Impact of Risk Perception and Financial Literacy on Gen Z Investors' Investment Decision-Making in Jabodetabek Region - Sesri Sellinai; Etty Zuliawati Zed; Tri Mulyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study investigates how Gen Z investors in the Jabodetabek region make investment decisions based on their perceptions of risk and financial literacy. A survey design was used to gather information from 150 Gen Z investors. To evaluate the proposed correlations, The study used partial least squares structural equation modeling, or PLS-SEM. The findings show that while risk perception has a negative impact on investing decisions, financial literacy has a favorable impact. The study also reveals that the association between risk perception and Financial literacy moderates investment decision-making. These results imply that even when young investors confront significant perceived risks, improving their financial literacy can help them make better investing decisions. The report provides insightful information for lawmakers and financial institutions looking to promote ethical investing practices in young adults.